探讨新加坡地缘性组织的功能转变 ：以新加坡广惠肇碧山亭为例 = Evolution of Chinese Clan Associations in Singapore : a case study on Singapore Kwong Wai Siew Peck San Theng - 黄诗颖 Ng, Shi Ying (Nanyang Technological University, 2021)
和世界各地的华人地缘性组织相似，新加坡的华人地缘性组织也充当了协助华人移民与家人和家乡维持联系的角色。但是，历经将近两世纪的蜕变以及全球化所带来的发展与冲击，新加坡的地缘性组织不仅需要调整其功能，甚至在建国后也陷入了边缘化境地。本文将通过新加坡广惠肇碧山亭这则案例，探讨该组织在建国后的运营模式变化如何反映其功能的转变，指出该组织的功能重心从管理安葬事宜转向弘扬华族文化的事务上。接着，透过内外因素分析，本文则进一步探析地缘性组织在建国后式微的成因和其未来的发展趋势，并且论证其式微的主要因素是因为国人无法对地缘性组织产生认同感。Similar to Chinese clan associations in other parts of the world, Chinese clan associations in Singapore are also known to play a pivotal role in helping Chinese immigrants to maintain connections with their homeland and family while overseas. However, nearly two centuries later, with rapid globalisation taking place, not only did the key role of Chinese clan associations changed tremendously, but clan associations are also facing challenges in keeping up with the times. Using Singapore Kwong Wai Siew Peck San Theng (KWS-PST) as a case study, this paper addresses changes in the key role of locality-based clan associations since Singapore’s independence. In-depth analysis on internal and external factors affecting the change shall render insights on how KWS-PST’s key role has evolved beyond cemetery and columbarium management to promoting Chinese culture. Based on the analysis of the aforementioned factors, this paper further discusses the future development of clan associations, whilst arguing the main reason leading to its decline today is due to the Chinese community in Singapore not being able to identify a sense of belonging with the clan associations.